Estratégias Metacognitivas Para Análise De Assunto: Aspectos teóricos de superestrutura e esquemas sobre textos literários infanto-juvenis - Alves, Roberta Caroline Vesú [UNESP]; De Brito Neves, Dulce Amélia; Fujita, Mariângela Spotti Lopes [UNESP]; De Moraes, João Batista Ernesto [UNESP] (My University, 2016)
The subject analysis in context of Documentary Analysis of Content, specifically identifying themes of infant-juvenile literary texts, require metacognitive strategies. Therefore, this study aimed to analyze some theoretical aspects of text and discourse which allow elucidating metacognitive strategies, schemes and superstructure of current infant-juvenile literature, with narrative text in prose, using the methodology of exploratory study. We analyzed as a result that superstructure of infant-juvenile literature may correspond in some respects to Generative Sense Course, which offers the means to be used as metacognitive strategies, identifying themes in Documentary Analysis of Content. We also emphasize that superstructure can indicate what should be considered as mental schemes for identifying structure and theme of texts.
Metacognitive strategies for analysis of subject: Theoretical aspects of superstructure and schemes of infant-juvenile literary texts
Keywords: Generative Sense Course; Metacognition; Textual superstructure